Detection of exon 5 c.577del variant of human erythropoietin gene in whole blood, dried blood spots and urine samples for doping control - Donati, Francesco; Concetti, Livia; de la Torre, Xavier; Zhou, Xinmiao; Zhang, Lisi; Botrè, Francesco (Frontiers in Analytical Science, 2023)
In doping control, the presence of the exon5 c.577del variant in the human erythropoietin gene may be a confounding factor in the interpretation of the results from the analytical method currently in force for the detection of human recombinant erythropoietin, based on immunoelectrophoresis on SDS-PAGE. This variant, determining the transcription of a higher molecular weight protein, can erroneously suggest the presence of recombinant erythropoietin in a biological sample, causing the possibility of a false positive result. Although the variant was now identified only in East Asian populations and with a very low frequency, it can be a threat to the reliability of current anti-doping tests. We have implemented a genetic test to identify the presence of this variant in the biological samples that are presently collected for anti-doping analysis (whole blood, urine and dried blood spots). The test is based on the Sanger sequencing of the human erythropoietin gene exon 5 in which the c.577del variant falls. It has a specificity of 100% and allows to obtain the identification of the possible presence of the variant starting from 100pg of genomic DNA extracted from each biological sample. The efficacy of the test has been confirmed by the analysis of real samples from subjects showing and not showing the exon c.577del variant.